The Role of Networking in the Internationalization of Indonesian SMEs - Revindo, Mohamad Dian; Indrawati, Sri Mulyani; Hambali, Sean (Universitas Negeri Semarang, 2019)
Indonesian SMEs are less able to take advantage of foreign market opportunities than their large counterparts. This study analyses the internationalization of Indonesian SMEs, particularly the differences between exporting and non-exporting SMEs in terms of their network relationships. Primary data was obtained from survey questionnaires in Jawa, Madura and Bali regions, yielding usable responses from 271 exporting SMEs and 226 non-exporting SMEs. Our results suggest that exporters on average have twice as many frequencies of interaction with various external actors than those of their non-exporting counterparts. Exporting and non-exporting SMEs also differ in the way they interact and maintain relationships with external actors. The exporting SMEs utilize various types of interactions including regular and irregular, as well as formal and informal ones, with various external actors in the network. In contrast, non-exporting SMEs are more dependent on personal relations with key persons in various governmental and private institutions. The policy and managerial implications of the findings are discussed.